2014
DOI: 10.1088/1475-7516/2014/03/042
|View full text |Cite
|
Sign up to set email alerts
|

Isotropy theorem for arbitrary-spin cosmological fields

Abstract: We show that the energy-momentum tensor of homogeneous fields of arbitrary spin in an expanding universe is always isotropic in average provided the fields remain bounded and evolve rapidly compared to the rate of expansion. An analytic expression for the average equation of state is obtained for Lagrangians with generic power-law kinetic and potential terms. As an example we consider the behavior of a spin-two field in the standard Fierz-Pauli theory of massive gravity. The results can be extended to general … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 51 publications
2
33
0
Order By: Relevance
“…Thus, as shown in [57] the average geometry generated by a rapidly oscillating massive abelian vector field is isotropic and evolves as in a matter dominated universe. If the vector field is responsible for all the DM contribution, its amplitude will be given by 20) with Ω c the CDM density parameter and ρ c = 3H 2 0 /(8πG) the critical density.…”
Section: Jhep02(2017)064mentioning
confidence: 88%
See 3 more Smart Citations
“…Thus, as shown in [57] the average geometry generated by a rapidly oscillating massive abelian vector field is isotropic and evolves as in a matter dominated universe. If the vector field is responsible for all the DM contribution, its amplitude will be given by 20) with Ω c the CDM density parameter and ρ c = 3H 2 0 /(8πG) the critical density.…”
Section: Jhep02(2017)064mentioning
confidence: 88%
“…Fortunately, a general result [57] shows that for massive fields without self interactions and masses much larger than the expansion rate, the average energy-momentum tensor is isotropic and behaves as CDM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the work on ultralight fields has been mainly concerned with scalar fields, there are recent results on higher spin fields. It has been shown that abelian vectors at the background [22] and perturbation level [23], non-abelian vectors [24] and arbitrary-spin fields [25] behave in a similar way. Interestingly, the results of [25] show that it is possible to achieve an isotropic model of higher-spin dark matter as long as it is rapidly oscillating.…”
Section: Jhep08(2018)073mentioning
confidence: 99%